2019
DOI: 10.1021/acsomega.9b00763
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Temperature NO Adsorber Derived from Pyrolysis of Co-MOF(ZIF-67)

Abstract: Co-, Ni-, and Zn-containing MOFs are prepared and then pyrolyzed to generate materials for ambient temperature NO adsorption. Materials containing Co are much more efficient for NO adsorption than those containing Ni and Zn; therefore, Co is identified as the active phase. The best performing material studied here achieves 100% low concentration (10 ppm) NO adsorption for more than 15 h under a weight hourly space velocity of 120 000 mL g –1 h –1 . Powder X-ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Sun et al evaluated several porous materials, including MOFs and ZIFs, for the removal of SO 2 and NOx from flue gases using molecular simulations . They concluded that ZIF-8 exhibited moderate NOx adsorption performance at 100 kPa and 313 K. However, the experimental results of Lin et al revealed that the adsorption capacity of MOFs for trace NO in exhaust was negligible …”
Section: Introductionmentioning
confidence: 99%
“…Sun et al evaluated several porous materials, including MOFs and ZIFs, for the removal of SO 2 and NOx from flue gases using molecular simulations . They concluded that ZIF-8 exhibited moderate NOx adsorption performance at 100 kPa and 313 K. However, the experimental results of Lin et al revealed that the adsorption capacity of MOFs for trace NO in exhaust was negligible …”
Section: Introductionmentioning
confidence: 99%
“…3c shows characteristic peaks of Co 0 (778.4 eV), Co 3+ (779.8 and 794.2 eV), and Co 2+ (781.4 and 798.1 eV), and along with satellite peaks (786.5 and 803.2 eV). 40 Most of the Co is present in oxidized states, largely as a result of the oxidization of the Co nanoparticles in air. 41 The XPS of C 1s (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…12 The low-temp peak (∼120°C) can be assigned to the weakly adsorbed NO and the other to more stable NO-adsorbed species due to the formation of nitrites and nitrates species. 46,47 Only small desorption features of NO x were detected for the poisoned catalysts, in the low temperature region. The total amounts of NO x desorption (equal to storage) were calculated and are displayed in Fig.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%